2010
DOI: 10.1111/j.1365-3164.2010.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a surgical scrub including 2% chlorhexidine acetate for canine superficial pyoderma

Abstract: The clinical efficacy of a surgical scrub containing 2% chlorhexidine acetate (2CA; Nolvasan® Surgical Scrub; Fort Dodge Animal Health, USA) was evaluated for the topical management of canine superficial pyoderma. The first study was a randomized, double-blind, controlled trial. The control was a shampoo containing 4% chlorhexidine gluconate (4CG; Skin Clinic Shampoo; CHD MEDICS, Goyang, Korea). Ten dogs with symmetrical lesions of canine superficial pyoderma were allocated to receive either 2CA or the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 12 publications
0
51
1
Order By: Relevance
“…Previous studies have shown that 2-4% chlorhexidine is an effective treatment for superficial pyoderma in some, but not all, dogs. [2][3][4]27 There are a number of possible explanations for discrepancies between in vivo antiseptic efficacy and in vitro susceptibility. Chlorhexidine might not have good penetration into the skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that 2-4% chlorhexidine is an effective treatment for superficial pyoderma in some, but not all, dogs. [2][3][4]27 There are a number of possible explanations for discrepancies between in vivo antiseptic efficacy and in vitro susceptibility. Chlorhexidine might not have good penetration into the skin.…”
Section: Discussionmentioning
confidence: 99%
“…These samples have been used in previous studies. [2][3][4] Pyoderma was confirmed based on clinical signs, cytological findings and bacterial culture. Samples for bacterial culture and susceptibility testing were collected from skin lesions compatible with pyoderma.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments for canine superficial pyoderma are mainly systemic antimicrobials, particularly cephalosporins, 3 although multidrug‐resistant mecA ‐positive Staphylococcus pseudintermedius has been emerging throughout the world 4,5 . The bisbiguanide antiseptic chlorhexidine has been considered an effective agent for treating canine superficial pyoderma, 6 and we have demonstrated the efficacy of 2% chlorhexidine acetate (2CA; Nolvasan ® Surgical Scrub; Fort Dodge Animal Health, Fort Dodge, IA, USA) monotherapy for canine superficial pyoderma associated with cefalexin‐resistant Staphylococcus intermedius 5 . One of the manufacturers of the 2% chlorhexidine product recommends 57 mL/m 2 body surface area; however, there has been no investigation to assess the appropriate dose of 2CA for canine superficial pyoderma.…”
Section: Introductionmentioning
confidence: 99%
“…Surface and superficial pyoderma, otitis and skin infections involving MDR staphylococci are the main conditions for which topical treatment is recommended. 28,29 A review published in Veterinary Dermatology in 2012 showed that good-quality studies are sparse and that there is a need for more randomized controlled trials using topical products. 30 However, the review found good evidence for efficacy of 2-4% chlorhexidine and benzoyl peroxide shampoos.…”
Section: Resisting the Resistance: Topical Antimicrobial Treatment (Amentioning
confidence: 99%